ENTERPRISE RISKS MANAGEMENT IN MODERN CONDITIONS - Kochkodan, V. B.; Petryna, M. Yu. (The actual problems of regional economy development, 2024)
The article is aimed at researching problems related to enterprise risk management in modern conditions. The purpose of the article is to consider the features of risk management at the enterprise in conditions of uncertainty, in order to increase its adaptability and flexibility, as well as to determine the main principles and management methods that allow a quick response to existing and potential threats and minimize the negative impact of risks on the enterprise's activities. The following research methods were used in the research process: theoretical generalization - to form definitions of concepts, general approaches and principles; analysis and synthesis; modeling - to form a model of the risk management process. To realize the set goal, the concepts’ definitions of "risk" and "risk management" were considered. The key conditions under which the risk assessment process will be most effective were formulated. The principles, compliance with which will contribute to enterprise’s successful risk management, were outlined. It was established that risk management requires careful development of strategy and tactics, which must be constantly coordinated with other system parameters and economic criteria of the enterprise's efficiency. The scientific novelty of the conducted research consists of solving tasks that have theoretical and practical significance in enterprise risk management field in modern conditions. The following tasks were solved to achieve the set goal: - Aspects of risk concept in the economic sphere are considered, including risk as a danger or threat, risk as an opportunity and risk as uncertainty. - The purpose of enterprise’s risk management is determined and it is aimed at preventing problems or negative consequences through effective crisis management and avoiding additional costs. - The risk management policy was established and it includes various methods and techniques aimed at reducing the risk of making wrong decisions and minimizing negative consequences. - The process of risk management was considered and it was established that it is cyclical and includes a sequence of well-defined stages, which help entrepreneurs identify business risks: risk identification, risk analysis, risk assessment, formulation of an action plan, mitigating the impact of risk, monitoring and controlling risks. - Risk management methods were investigated, including: risk avoidance (deviation from risk or prevention of its occurrence); risk neutralization through its transfer (includes insurance, hedging and financial guarantees), reduction (includes diversification, limitation, optimization and localization) or preservation (includes the creation of a reserve fund, self-insurance and the creation of insurance reserves for stocks of raw materials and cash).